(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
Agriculture is a basic profession in our country to give the production that the local consumer needs. Through the five-year plan, Libya aims to modernize the agricultural sector and keep pace with the economic, social, and scientific changes taking place at the local and international levels. This plan will enable the country to increase the contribution of the agricultural sector and increase the rate of economic growth through employment. The project examines the agricultural environment of temperature, humidity, and irrigation control. The project works by voice commands, so that, the farmer is careful and knows the temperature and humidity, the proportion of water in the soil and all the information needed by voice commands. The environment will not be an obstacle to the production and growth of any plant, we can overcome the problem of scarcity of agricultural production, and can call a smart way to automate. The focus will be on providing a favourable atmosphere for plants. Monitoring the environment and providing solutions in line with climate change and real-time follow-up is an important factor in smart farming. A smart way to automate the farming process can be called smart farming. Using the system automatically enables you to eliminate potential crop threats by reducing human intervention, increasing productivity, improving a product, and providing private nurseries and farms to Agriculture Research Centre and farmers. The focus will be on providing a favourable environment for plants. This project includes many features such as a device, humidity, temperature control, intruder risk, water flow and monitoring using different sensors.